Green and ultra-light magnesium foam processed using oyster shell powder as blowing agent - Isakovic, Jonas; Dieringa, Hajo; Pröfrock, Daniel; Ben Khalifa, Noomane (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This study investigates the manufacturing process and material properties of a closed-cell “green” magnesium foam produced by the melt-foaming process using oyster shell powder (CaCO3) as a blowing agent. Oyster shells are a by-product of food and jewellery production, which are considered to be waste and are usually stored in landfills. Alternative uses for the shells are therefore being sought in order to return them to the raw material cycle. A Mg-1Ca alloy is used as the matrix alloy. Magnesium and calcium are elements that are dissolved in seawater and can therefore be extracted from it, for example in desalination plants. We present here the first magnesium foam that has been obtained from magnesium and calcium using oyster shell powder as a blowing agent. This means the foam consists of naturally extractable components, that could also be generated from the Atlantic Ocean or the North Sea, for example. Since the material does not contain any other contamination, e.g. from a technical blowing agent, returning it to marine environment after the end of life by dissolving it in seawater is expected to not cause any ecological or economic damage. Here the production process is described and the dissolution rate in seawater is investigated. The composition and structure of the foam and its mechanical properties are examined. The foam has a fairly homogeneous pore structure, whereby the pore size in the upper area of the foam is slightly increased due to the drainage effect, which also has an effect on the mechanical properties.
Keywords: Magnesium Foam; Oyster Shell Powder; Ultralightweight; Structural; Circular Economy; Net Zero; Recycling; Natural Product